Hubungan Pola Makan Dengan Kejadian Gastritis di Puskesmas Bojonggede Kabupaten Bogor - Tio Maulana; Indri Sarwili (PT. Hasba Edukasi Mandiri, 2025)
Background: Gastritis is an inflammation of the gastric mucosa that is acute, chronic, diffuse or localized, with characteristics of anorexia, a feeling of fullness in the stomach (bloating), discomfort in the epigastrium, nausea, and vomiting. Purpose: this study was to determine whether or not there is a relationship between diet and the incidence of gastritis at the Bojonggede Community Health Center, Bogor Regency, in 2022. Method: This type of research is an analytic observational study with a case control study approach. Research Hypothesis: The results of the study Diet with gastritis incidence at Bojonggede Health Center obtained a correlation coefficient value of .737 which means that the interpretation of the correlation strength is strong or high. As for the significance value of .048, if the sig value is 0.048 < 0.1, there is a correlation or relationship between diet and the incidence of gastritis in Puskemas Bojonggede, Bogor Regency in 2022.